Development of Statistical Model to Predict Ra and Rz in the Laser Cutting - M. M., Noor; K., Kadirgama; M. M., Rahman; M. R. M., Rejab; M. S. M., Sani; R. A., Bakar; T. T., Mon (2009)
Laser cutting is one of the advances machining on material remover process.This paper explores the prediction model of surface roughness (Ra) and roughness height (Rz) of laser beam cutting on acrylic sheets. Box-Behnken design based Response Surface Method (RSM) was used to predict the effect of laser cutting parameters which are laser power, cutting speed and tip distance on Ra and Rz. The predictive models are good agreement with experimental results. The first order equation revealed that the power requirement was the dominant factor followed by tip distance and cutting speed respectively. This observation indicates that the potential of using RSM in predicting cutting parameters thus eliminating the need for exhaustive cutting experiments to obtain the optimum cutting condition and enhance the surface roughness.